2012
DOI: 10.1590/s0103-64402012000100010
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo radiographic evaluation of the accuracy of Apex and iPex electronic Apex locators

Abstract: The aim of this study was to evaluate in vivo the clinical applicability of two electronic apex locators (EALs) - Apex (Septodont) and iPex (NSK) - in different groups of human teeth by using radiography. The working lengths (WLs) of 100 root canals were determined electronically. The EAL to be used first was chosen randomly and a K-file was inserted into the root canal until the EAL display indicated the location of the apical constriction (0 mm). The K-file was fixed to the tooth and a periapical radiograph … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…Electronic root canal length measurement devices (ERCLMDs) are considered efficient tools for this purpose 12,15,18,26,28 , achieving precision percentages upwards of 80% ex vivo 2,4,6,9,17-20,23-26 and in vivo 8,23,27,29,30 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electronic root canal length measurement devices (ERCLMDs) are considered efficient tools for this purpose 12,15,18,26,28 , achieving precision percentages upwards of 80% ex vivo 2,4,6,9,17-20,23-26 and in vivo 8,23,27,29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…However, little information is available regarding its technical specifications, aside from the fact that it utilizes two different signal frequencies. Both the Mini Apex Locator and the iPex have demonstrated satisfactory clinical results, despite the relative lack of information on their operating mechanisms, especially with regards to how these devices electronically interpret the impedance values obtained in the different frequencies during measurements within the canal 4,16,18,23,24,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies 19,30,34 compared the accuracy of different models of EALs with radiographic root canal length determination and showed that the electronic methods provided the best results. In addition, the EALs have the advantage of reducing the number of radiographs required to establish the apical limit of root canal instrumentation in clinical practice 11,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown great performance of electronic apex locators (12,13). However, the most common method to determine working length combines knowledge of root lengths, tactile discrimination, assessment of a preoperative radiograph and a radiograph taken with files placed in the root canal (14).…”
Section: Discussionmentioning
confidence: 99%